The Churchyard Memorials of St Andrews (Proceedings of the Society of Antiquaries of Scotland, 1911)
St Andrews, and particularly its cathedral graveyard, is extremely rich in the variety and value of its monumental remains. It presents examples of nearly every style of tombstone, and of many original forms of symbolism. Earlier published accounts are expanded upon and new discoveries are described. Many of the stones are now in the Cathedral Museum. In addition to more than fifty table stones there is an immense number of Celtic, mediaeval, and later details gathered from different quarters of the city. Mortsafes and coffin guards are also included.